Practices of political participation. Socialization experiences of young people in night schools (Praxis Educativa, 2017)
In this article we will analyze one of the axes of interviews to young people from two secondary night schools in Viedma, Rio Negro, Argentina, starting from questionings intended to know the practices of political participation of young people, as socialization experiences at night middle schools. In the practices of political participation it is possible to visualize different strategies on the part of students: non-participation, performance as class delegates, in the Students’ Union, among others. Among the results it was noted that, for some young people, participating in the Students’ Union is more related to the necessity of building a space with certain autonomy in regard to adults, than to a political strategy.
Keywords: young people; education; school; politics; participation